A Study on the Effect of Sponsorship of Local Culture and Arts on Corporate Image - Lee, Jin-Woo (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: Many good works are disappearing because they do not receive sponsorship. In order to revitalize cultural and artistic performances, it is necessary to reduce the distribution of free invitations.